A negative electrode material, a preparation method thereof and a lithium ion battery
By growing nitrogen-doped carbon nanotubes and generating an artificial SEI layer on the surface of a silicon substrate, the problems of volume expansion and lithium-ion loss during the lithium insertion/extraction process of silicon-based anode materials are solved, thereby improving the conductivity of the anode materials and battery performance.
Patent Information
- Application Number
- CN202311708274.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-12
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-12-12
AI Technical Summary
Failure issues in silicon-based anode materials caused by volume expansion and lithium-ion loss during lithium insertion/extraction include active material shedding and battery performance degradation.
By employing a combined structure of nitrogen-doped carbon nanotubes and an artificial SEI layer, nitrogen-doped carbon nanotubes are grown in situ on the surface of a silicon substrate, and an artificial SEI layer is generated using a lithiation reagent. This improves conductivity, provides a lithium source, and mitigates volume expansion and lithium-ion loss.
It significantly improves the conductivity and cycle performance of the negative electrode material, reduces volume expansion, and enhances the battery's initial efficiency and rate performance.
Smart Images

Figure CN117936726B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a negative electrode material, its preparation method, and a lithium-ion battery. Background Technology
[0002] Currently, a key development trend in automotive lithium-ion batteries is to improve energy density, but the capacity of traditional graphite anodes is nearing its limit. Silicon-based anodes, on the other hand, possess a high theoretical energy density (3579 mAh·g). -1 The silicon anode has a working potential of approximately 0.37V, nearly ten times that of graphite anodes, resulting in high battery energy density and improved operational safety. During charging and discharging, lithium ions can intercalate and deintercalate from silicon in all directions, whereas the intercalation and deintercalation channels in graphite anodes are only located at the layered end faces. This gives silicon anodes superior fast-charging capabilities. Furthermore, silicon is abundant in the Earth's crust. Due to these advantages, silicon is widely used in lithium-ion batteries.
[0003] However, silicon has poor conductivity, and during the lithium insertion / extraction process, it undergoes a huge volume expansion, which can reach over 300%. This leads to material pulverization during cycling, with active material detaching from the current collector. Due to its huge volume expansion, the SEI film continuously breaks down and reassembles, exposing silicon to the electrolyte. This repeated formation of the SEI film consumes a large amount of electrolyte and lithium ions, resulting in the continuous consumption of active lithium and ultimately causing capacity loss. Consequently, it affects the performance of lithium-ion batteries, causing irreversible capacity loss, thus impacting battery capacity and lifespan.
[0004] In view of this, this invention is hereby proposed. Summary of the Invention
[0005] The primary objective of this invention is to provide an anode material that fully or partially solves the problems of silicon-based anode failure and active material shedding caused by volume expansion and lithium ion loss during the lithium insertion / extraction process.
[0006] The second objective of this invention is to provide a method for preparing a negative electrode material, which improves the conductivity of the negative electrode material, alleviates the volume expansion of silicon, and achieves lithium replenishment of the negative electrode.
[0007] The third objective of this invention is to provide a lithium-ion battery with high initial efficiency, excellent cycle performance, and high rate performance.
[0008] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:
[0009] The present invention provides a negative electrode material, comprising a core and a coating layer covering the surface of the core;
[0010] The core includes a silicon substrate and nitrogen-doped carbon nanotubes attached to the surface of the silicon substrate;
[0011] The coating layer includes an artificial SEI layer.
[0012] Furthermore, it includes at least one of the following features (1) to (4);
[0013] (1) The nitrogen-doped carbon nanotubes contain 1 wt% to 5 wt% nitrogen.
[0014] (2) The artificial SEI layer includes lithium silicate and film-forming additives;
[0015] (3) The mass ratio of the lithium silicate to the film-forming additive is (1-10):1;
[0016] (4) The film-forming additives include at least one of LiTFSI, LiBOB, LiBODFP, LiTFOP, LiODFB, LiPO2F2, LiFSI, FEC, VEC, ES and VC.
[0017] Furthermore, the mass ratio of the silicon substrate to the nitrogen-doped carbon nanotubes is (2-10):1;
[0018] And / or, the mass ratio of the silicon substrate to the artificial SEI layer is (10-50):1.
[0019] The present invention also provides a method for preparing the negative electrode material as described above, comprising the following steps:
[0020] S1. Nitrogen-doped carbon nanotubes are grown in situ on the surface of a silicon substrate to obtain Si@N-CNTs;
[0021] S2. The Si@N-CNTs are impregnated in a lithium-ionizing agent to obtain the negative electrode material.
[0022] Further, in step S1, nano-silicon is immersed in a solution containing a catalyst precursor to obtain nano-silicon with a catalyst precursor attached to its surface.
[0023] The nano-silicon with catalyst precursors attached to its surface is sintered in a hydrogen atmosphere and then calcined in an atmosphere containing carbon and nitrogen sources to obtain the Si@N-CNTs.
[0024] Further, in step S1, the sintering temperature is 600–1200°C, and the sintering time is 1–10 h;
[0025] And / or, the calcination temperature is 600–1200°C, and the calcination time is 1–10 h.
[0026] Furthermore, in step S2, before the impregnation, the method further includes: immersing the Si@N-CNTs in an acidic solution for impurity removal.
[0027] Furthermore, step S2 includes at least one of the following features (1) to (5);
[0028] (1) The lithium-ionizing agent includes elemental lithium, aromatic hydrocarbons, film-forming additives and solvents;
[0029] (2) The aromatic hydrocarbons include at least one of naphthalene and its derivatives, biphenyl and its derivatives, terphenyl and its derivatives, tetraphenyl and its derivatives, anthracene and its derivatives, phenanthrene and its derivatives, and naphthalene and its derivatives;
[0030] (3) In the lithium-ionizing agent, the content of the aromatic hydrocarbon is 0.01 to 20 mol%.
[0031] (4) In the lithium-ionizing agent, the content of the film-forming additive is 0.01 to 1 mol / L;
[0032] (5) The molar ratio of the elemental lithium to the aromatic hydrocarbon is (3-8):1.
[0033] Furthermore, in step S2, the soaking time is 5 to 15 minutes.
[0034] The present invention also provides a lithium-ion battery comprising the negative electrode material as described above.
[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0036] 1. The anode material of the present invention, by attaching nitrogen-doped carbon nanotubes to the surface of a silicon substrate, utilizes the porous network and mechanical strength of the nitrogen-doped carbon nanotubes to slow down the volume expansion of the silicon-based anode material and improve the conductivity of the anode material; the artificial SEI layer on the surface provides a lithium source for the anode material, solving the problem of lithium ion loss.
[0037] 2. The method for preparing the anode material of the present invention involves simultaneously growing nitrogen-doped carbon nanotubes on the surface of a silicon substrate using chemical vapor deposition. The resulting nitrogen-doped carbon nanotubes have higher purity, stronger bonding with the silicon substrate, and better conductivity. This alleviates the volume expansion problem of the anode material during lithium insertion / extraction and improves its conductivity during charge-discharge cycles. By impregnating the anode material with a lithiation reagent and replenishing lithium through a redox reaction, an artificial SEI layer is generated on the surface, achieving a pre-lithiation effect. This solves the lithium-ion loss problem while slowing down the volume expansion of silicon. Attached Figure Description
[0038] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0039] Figure 1 This is a schematic diagram of the structure of the negative electrode material of the present invention.
[0040] Figure 2 This is a morphology diagram of Si@N-CNTs in Embodiment 1 of the present invention. Detailed Implementation
[0041] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0042] See Figure 1 In some embodiments of the present invention, a negative electrode material is provided, including a core and a coating layer covering the surface of the core;
[0043] The core consists of a silicon substrate (Si) and nitrogen-doped carbon nanotubes (N-CNTs) attached to the surface of the silicon substrate;
[0044] The coating layer includes a synthetic SEI layer.
[0045] The anode material of this invention, by attaching nitrogen-doped carbon nanotubes to the surface of a silicon substrate, utilizes the porous network and mechanical strength of the nitrogen-doped carbon nanotubes to mitigate the volume expansion problem of silicon-based anode materials. Doping with nitrogen atoms alters the electronic structure of the carbon nanotubes; when nitrogen is substituted for doping, a hybrid state is formed, and the provided valence electrons occupy the conduction band of the carbon nanotubes, causing the Fermi level to migrate to the conduction band, thus improving the conductivity of the carbon nanotubes and consequently the conductivity of the anode material. A uniform, stable, dense, and lower-resistance artificial SEI layer provides a lithium source for the anode material, solving the problem of lithium-ion loss, mitigating volume expansion, suppressing battery gas production, and simultaneously improving the lithium-ion transport rate and battery rate performance.
[0046] The anode material of this invention solves the problems of volume expansion and lithium ion loss, active material shedding, and failure of silicon-based anode materials during the lithium insertion / extraction process.
[0047] Carbon nanotubes possess advantages such as large specific surface area, good electrical conductivity, high mechanical strength, and good stability, leading to their wide application in new energy vehicle industry, 3C digital industry, semiconductor industry, and power infrastructure. Doping with nitrogen atoms can alter the electronic structure of carbon nanotubes. Nitrogen substitution during doping forms hybrid states, and the provided valence electrons occupy the conduction band of the carbon nanotube, causing the Fermi level to shift towards the conduction band, which improves the conductivity of the carbon nanotube. This, in turn, improves the conductivity of the anode material while mitigating volume expansion.
[0048] The significant volume expansion of silicon anodes during cycling can cause the SEI film to rupture, exposing the internal active lithium and leading to repeated SEI film formation and loss of active lithium. This invention addresses this by creating an artificial SEI layer, enabling pre-lithiation of the anode material and mitigating the volume expansion of silicon during lithium insertion / extraction, resulting in a significant reduction in volume expansion during charge / discharge.
[0049] In some embodiments of the present invention, the nitrogen content in nitrogen-doped carbon nanotubes is 1 wt% to 5 wt%; preferably, the nitrogen content in nitrogen-doped carbon nanotubes is 2.5 wt% to 3.5 wt%.
[0050] In some embodiments of the present invention, the artificial SEI layer includes lithium silicate and film-forming additives.
[0051] The artificial SEI layer with lithium silicate as the main component solves the problem of lithium ion loss and slows down volume expansion. The addition of film-forming additives helps to generate a more uniform, stable, dense, and lower resistivity SEI film, which can suppress battery gas production, while improving lithium ion transport rate and battery rate performance.
[0052] In some embodiments of the present invention, the mass ratio of lithium silicate to film-forming additive is (1 to 10):1; typically, but not limitingly, for example, the mass ratio of lithium silicate to film-forming additive can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any combination thereof; preferably, the mass ratio of lithium silicate to film-forming additive is (7 to 9):1.
[0053] In some embodiments of the present invention, the film-forming additive includes at least one of LiTFSI, LiBOB, LiBODFP, LiTFOP, LiODFB, LiPO2F2, LiFSI, FEC, VEC, ES, and VC.
[0054] In some embodiments of the present invention, the mass ratio of silicon substrate to nitrogen-doped carbon nanotubes is (2 to 10):1; typically, but not limitingly, for example, the mass ratio of silicon substrate to nitrogen-doped carbon nanotubes can be 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any combination thereof; preferably, the mass ratio of silicon substrate to nitrogen-doped carbon nanotubes is (2 to 3):1.
[0055] In some embodiments of the present invention, the mass ratio of the silicon substrate to the artificial SEI layer is (10-50):1; typically, but not limitingly, for example, the mass ratio of the silicon substrate to the artificial SEI layer can be a range of 10:1, 20:1, 30:1, 40:1, 50:1 or any two of these; preferably, the mass ratio of the silicon substrate to the artificial SEI layer is (15-20):1.
[0056] In some embodiments of the present invention, a method for preparing the above-mentioned negative electrode material is also provided, comprising the following steps:
[0057] S1. Nitrogen-doped carbon nanotubes are grown in situ on the surface of a silicon substrate to obtain Si@N-CNTs;
[0058] S2 and Si@N-CNTs are impregnated in a lithium-ionizing agent to obtain the anode material.
[0059] The main methods for preparing carbon nanotubes include the electric arc method, laser evaporation method, and chemical vapor deposition method. Among them, carbon nanotubes prepared by chemical vapor deposition have higher purity because the residual reactants are gases that can leave the system, and the reaction temperature is not very high.
[0060] There are two main methods for preparing silicon / carbon nanotube composite materials: one is to mix carbon nanotubes with nano-silicon, and the other is to grow carbon nanotubes directly on a silicon matrix.
[0061] This invention employs chemical vapor deposition to simultaneously grow nitrogen-doped carbon nanotubes on a silicon substrate. The resulting nitrogen-doped carbon nanotubes have higher purity, stronger adhesion to the silicon substrate, and better conductivity. After growing nitrogen-doped carbon nanotubes on the silicon substrate, the high mechanical strength of the carbon nanotubes alleviates the volume expansion problem of the silicon-based anode material during lithium insertion / extraction, while also improving the conductivity of the anode material during charge / discharge cycles.
[0062] This invention employs a lithium-ion reagent to impregnate the negative electrode material and replenish lithium through a redox reaction, thereby generating an artificial SEI layer on its surface and achieving a pre-lithiation effect. This solves the problem of lithium-ion loss while mitigating the volume expansion of silicon.
[0063] In some embodiments of the present invention, in step S1, nano-silicon is immersed (completely soaked) in a solution containing a catalyst precursor to obtain nano-silicon with a catalyst precursor attached to its surface.
[0064] Nano-silicon with catalyst precursors attached to its surface is sintered in a hydrogen atmosphere and then calcined in an atmosphere containing carbon and nitrogen sources to obtain Si@N-CNTs.
[0065] This invention involves immersing nano-silicon in a solution containing a catalyst precursor, allowing the catalyst precursor to uniformly adhere to the surface of the nano-silicon; then sintering in a hydrogen atmosphere to reduce the catalyst precursor to a metallic element; and finally calcining in an atmosphere containing a carbon source and a nitrogen source, where the gaseous carbon source and nitrogen source undergo high-temperature catalytic decomposition, resulting in the in-situ growth of nitrogen-doped carbon nanotubes on the surface of the silicon substrate, thus obtaining Si@N-CNTs.
[0066] In some embodiments of the present invention, in step S1, the catalyst precursor includes at least one of nickel nitrate, cobalt nitrate, ferric nitrate, and copper nitrate; preferably, the catalyst precursor includes nickel nitrate.
[0067] In some embodiments of the present invention, in step S1, the mass ratio of nano-silicon to the catalyst precursor in the solution containing the catalyst precursor is 1:(2-10).
[0068] In some embodiments of the present invention, in step S1, the solvent in the solution containing the catalyst precursor includes acetone.
[0069] In some embodiments of the present invention, in step S1, the time for immersing nano-silicon in a solution containing a catalyst precursor is 1 to 2 hours.
[0070] In some embodiments of the present invention, step S1, after soaking, further includes drying; preferably, the drying temperature is 60-80°C.
[0071] In some embodiments of the present invention, in step S1, the sintering temperature is 600-1200°C and the sintering time is 1-10h; preferably, in step S1, the sintering temperature is 750-850°C and the sintering time is 1-3h.
[0072] In some embodiments of the present invention, in step S1, the heating rate of the sintering process is 3 to 10 °C / min; preferably 5 to 10 °C / min.
[0073] In some embodiments of the present invention, in step S1, during the sintering process, the flow rate of hydrogen gas is 10-50 mL / min.
[0074] In some embodiments of the present invention, in step S1, the carbon source includes at least one of methane, ethylene, acetylene, propylene, cyclic hydrocarbon benzene, xylene, and fullerene.
[0075] In some embodiments of the present invention, in step S1, the nitrogen source includes ammonia.
[0076] In some embodiments of the present invention, in step S1, during the calcination process, the gas flow rates of the carbon source and the nitrogen source are each independently 10-50 mL / min; preferably 25-35 mL / min; preferably, the gas flow time during the calcination process is 30-60 min.
[0077] In some embodiments of the present invention, in step S1, the calcination temperature is 600-1200°C and the calcination time is 1-10 hours; preferably, in step S1, the calcination temperature is 750-850°C and the calcination time is 1-3 hours.
[0078] In some embodiments of the present invention, in step S1, the heating rate of the calcination process is 3 to 10 °C / min; preferably 5 to 8 °C / min.
[0079] In some embodiments of the present invention, in step S1, after calcination, cooling is performed; preferably, the temperature is cooled to 30-60°C.
[0080] In some embodiments of the present invention, step S2, before wetting, further includes: immersing Si@N-CNTs in an acidic solution for impurity removal.
[0081] In some embodiments of the present invention, in step S2, the acidic solution includes at least one of dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid.
[0082] In some embodiments of the present invention, in step S2, the lithiation reagent includes elemental lithium, aromatic hydrocarbons, film-forming additives, and solvents.
[0083] This invention involves impregnating Si@N-CNTs into an organic lithium compound with added film-forming additives, and transferring lithium onto the Si@N-CNTs through a redox reaction to obtain a lithium-containing artificial SEI layer. This artificial SEI layer provides a lithium source for the silicon-carbon anode and slows down the volume expansion of silicon. The added film-forming additives make the formed artificial SEI layer more uniform, denser, and with lower interfacial resistance, while also suppressing gas generation in the battery.
[0084] The mechanism of SEI film formation is as follows: The redox reaction potential of Li-aromatic complex is very low. When silicon-carbon composite material is immersed in it, lithium ions can be extracted from the Li-aromatic complex. The extracted lithium ions can react with the material to form a lithium silicate shell, thus obtaining an artificial SEI layer. This achieves pre-lithiation of silicon-carbon composite material, alleviates the volume expansion of silicon during lithium insertion and extraction, and the added film-forming additives can make the formed artificial SEI layer more uniform and dense, with lower interface resistance. At the same time, it can suppress battery gas production, etc., and the lithium ion transport rate is faster, thus improving the battery rate performance.
[0085] In some embodiments of the present invention, in step S2, the aromatic hydrocarbon includes at least one of naphthalene and its derivatives, biphenyl and its derivatives, terphenyl and its derivatives, tetraphenyl and its derivatives, anthracene and its derivatives, phenanthrene and its derivatives, and naphthalene and its derivatives.
[0086] In some embodiments of the present invention, in step S2, the content of aromatic hydrocarbons in the lithiation reagent is 0.01 to 20 mol%. Typically, but not limitingly, for example, the content of aromatic hydrocarbons in the lithiation reagent can be 0.01 mol%, 0.5 mol%, 1 mol%, 5 mol%, 15 mol%, 20 mol%, or any combination thereof. Preferably, the content of aromatic hydrocarbons in the lithiation reagent is 8 to 12 mol%.
[0087] In some embodiments of the present invention, in step S2, the content of the film-forming additive in the lithiation reagent is 0.01 to 1 mol / L; the content of the film-forming additive in the lithiation reagent can be a range of 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.7 mol / L, 1 mol / L, or any combination thereof; preferably, the content of the film-forming additive in the lithiation reagent is 0.15 to 0.25 mol / L.
[0088] In some embodiments of the present invention, in step S2, the molar ratio of elemental lithium to aromatic hydrocarbon in the lithiation reagent is (3-8):1; typically, but not limitingly, for example, the molar ratio of elemental lithium to aromatic hydrocarbon is 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or any combination thereof; preferably, the molar ratio of elemental lithium to aromatic hydrocarbon is (3-5):1.
[0089] In some embodiments of the present invention, in step S2, the solvent includes at least one selected from dimethyl ether, diethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, 1,2-dimethoxyethane (DME), and tetrahydrofuran (THF).
[0090] In some embodiments of the present invention, in step S2, the soaking (complete immersion) time is 5 to 15 minutes.
[0091] In some embodiments of the present invention, a lithium-ion battery is also provided, comprising the above-described negative electrode material.
[0092] Example 1
[0093] The method for preparing the negative electrode material provided in this embodiment includes the following steps:
[0094] S1. Dissolve 2g of nickel nitrate in 50mL of acetone to obtain a solution containing the catalyst precursor; immerse 1g of nano-silicon in the above solution for 1h, remove it and dry it in an oven at 60℃ to obtain nano-silicon with the catalyst precursor attached to its surface.
[0095] The nano-silicon with catalyst precursor attached to its surface was placed in a furnace, and argon gas was introduced into the furnace at a flow rate of 50 mL / min for 30 min to remove air from the furnace. Then, hydrogen gas was introduced into the furnace at a flow rate of 20 mL / min, and the temperature was raised to 550℃ at a rate of 10℃ / min and held for 30 min.
[0096] Then, acetylene and ammonia gas were introduced into the furnace at a flow rate of 30 mL / min each. Simultaneously, the temperature was increased to 700℃ at a rate of 5℃ / min and held for 3 hours. After cooling to 60℃, the treated material was immersed in a 0.5 mol / L hydrochloric acid solution for 30 minutes to remove impurities, yielding Si@N-CNTs (with an N content of 4.3 wt%). The morphology of the Si@N-CNTs is as follows: Figure 2 As shown.
[0097] S2. Dissolve biphenyl and LiODFB in dimethyl ether, then add lithium sheets to obtain a lithiation reagent; in the lithiation reagent, the molar percentage of biphenyl is 10 mol%, the concentration of LiODFB is 0.2 mol / L, and the lithium content is 30 g / L; then 1 g of Si@N-CNTs is immersed in the above lithiation reagent for 10 min to obtain the negative electrode material.
[0098] Example 2
[0099] The preparation method of the negative electrode material provided in this embodiment is the same as that in Embodiment 1, except that in step S1, nickel nitrate is replaced with iron nitrate.
[0100] Example 3
[0101] The preparation method of the negative electrode material provided in this embodiment is the same as that in Embodiment 1, except that in step S1, nickel nitrate is replaced with copper nitrate.
[0102] Example 4
[0103] The method for preparing the negative electrode material provided in this embodiment is the same as in Embodiment 1, except that in step S1, methane and ammonia are introduced into the furnace at a flow rate of 30 mL / min for each of the methane and ammonia, and the temperature is raised to 900°C at a rate of 5°C / min and held for 2 hours.
[0104] Example 5
[0105] The method for preparing the negative electrode material provided in this embodiment is the same as in Embodiment 1, except that in step S1, ethylene and ammonia are introduced into the furnace at a flow rate of 30 mL / min for each of the ethylene and ammonia, and the temperature is raised to 800°C at a rate of 5°C / min and held for 3 hours.
[0106] Example 6
[0107] The method for preparing the negative electrode material provided in this embodiment is the same as in Embodiment 1, except that in step S1, xylene and ammonia are introduced into the furnace at a flow rate of 30 mL / min for each of the xylene and ammonia, and the temperature is raised to 800°C at a rate of 5°C / min and held for 3 hours.
[0108] Example 7
[0109] The method for preparing the negative electrode material provided in this embodiment is the same as in Embodiment 1, except that in step S1, fullerene and ammonia are introduced into the furnace at a flow rate of 30 mL / min for each of the fullerene and ammonia, and the temperature is raised to 800°C at a rate of 5°C / min and held for 3 hours.
[0110] Example 8
[0111] The preparation method of the negative electrode material provided in this embodiment is the same as that in Embodiment 1, except that in step S2, biphenyl is replaced with naphthalene, LiODFB is replaced with LiTFOP, and dimethyl ether is replaced with tetrahydrofuran.
[0112] Example 9
[0113] The preparation method of the negative electrode material provided in this embodiment is the same as that in Embodiment 1, except that in step S2, biphenyl is replaced with terphenyl and dimethyl ether is replaced with tetrahydrofuran.
[0114] Example 10
[0115] The preparation method of the negative electrode material provided in this embodiment is the same as that in Embodiment 1, except that in step S2, biphenyl is replaced with phenanthrene and LiODFB is replaced with LiPO2F2.
[0116] Example 11
[0117] The preparation method of the negative electrode material provided in this embodiment is the same as that in Example 1, except that in step S2, biphenyl is replaced with 3,3′,4,4′-tetramethylbiphenyl.
[0118] Comparative Example 1
[0119] The negative electrode material provided in this comparative example is nano-silicon.
[0120] Comparative Example 2
[0121] The negative electrode material provided in this comparative example is Si@N-CNTs, and its preparation method is the same as in Example 1.
[0122] Comparative Example 3
[0123] The negative electrode material provided in this comparative example includes the following steps:
[0124] 1g of nano-silicon was immersed in a lithiation reagent for 10 minutes to obtain a negative electrode material; wherein the lithiation reagent was the same as in Example 1.
[0125] Experimental Example 1
[0126] Battery assembly method: The negative electrode material, conductive carbon black and binder (SBR-CMC) are mixed according to the ratio of negative electrode material: SP:CMC:SBR = 95.5:1:1.5:2 (mass ratio). After being fully dispersed and uniform, a slurry is obtained. The slurry is uniformly coated on the current collector copper foil and placed in a vacuum drying oven at 120°C for 12 hours. After the oven cools naturally to room temperature, the electrode sheet is taken out and punched into a circular electrode sheet using a steel punching die. After weighing, it is placed in a glove box.
[0127] The experiment was conducted in an argon-filled glove box, where the water and oxygen content were both less than 0.1 ppm. A lithium metal sheet was used as the counter electrode, and an appropriate amount of electrolyte was added to assemble a CR2032 coin cell. After standing, the cell was tested.
[0128] Batteries were assembled using the negative electrode materials of Examples 1-11 and Comparative Examples 1-3, respectively, according to the battery assembly method described above. The performance of each battery was tested, and the results are shown in Table 1.
[0129] Battery testing method: Cut-off voltage 0~2.0V, first charge and discharge at a rate of 0.1C for 3 cycles, then charge and discharge at a rate of 0.5C for 100 cycles, and record the capacity retention rate.
[0130] Table 1
[0131]
[0132]
[0133] As can be seen from Table 1, the anode material of the present invention can significantly improve the first-cycle coulombic efficiency and capacity retention. This is because the carbon nanotubes grown on the silicon surface by CVD increase the conductivity of silicon and delay the volume expansion of silicon. The wetting of the highly reducing lithiation reagent causes the formation of an artificial SEI film on the silicon-carbon surface, which realizes the lithium replenishment of the anode, thereby solving the problem of low first-cycle efficiency of the anode material. Moreover, the artificial SEI film delays the volume expansion of silicon, thereby improving battery performance.
[0134] This description is intended to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode material, characterized in that, Includes the core and a covering layer covering the surface of the core; The core includes a silicon substrate and nitrogen-doped carbon nanotubes attached to the surface of the silicon substrate; The coating layer includes an artificial SEI layer; The artificial SEI layer includes lithium silicate and film-forming additives; The method for preparing the negative electrode material includes the following steps: S1. Nitrogen-doped carbon nanotubes are grown in situ on the surface of a silicon substrate to obtain Si@N-CNTs; S2. The Si@N-CNTs are impregnated in a lithium-ionizing agent to obtain the negative electrode material; In step S1, nano-silicon is immersed in a solution containing a catalyst precursor to obtain nano-silicon with a catalyst precursor attached to its surface. The nano-silicon with catalyst precursors attached to its surface is sintered in a hydrogen atmosphere and then calcined in an atmosphere containing carbon and nitrogen sources to obtain the Si@N-CNTs.
2. The negative electrode material according to claim 1, characterized in that, Includes at least one of the following features (1) to (3); (1) The nitrogen content in the nitrogen-doped carbon nanotubes is 1wt%~5wt%; (2) The mass ratio of the lithium silicate to the film-forming additive is (1~10):1; (3) The film-forming additives include at least one of LiTFSI, LiBOB, LiBODFP, LiTFOP, LiODFB, LiPO2F2, LiFSI, FEC, VEC, ES and VC.
3. The negative electrode material according to claim 1, characterized in that, The mass ratio of the silicon substrate to the nitrogen-doped carbon nanotubes is (2~10):1; And / or, the mass ratio of the silicon substrate to the artificial SEI layer is (10~50):
1.
4. The method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Nitrogen-doped carbon nanotubes are grown in situ on the surface of a silicon substrate to obtain Si@N-CNTs; S2. The Si@N-CNTs are impregnated in a lithium-ionizing agent to obtain the negative electrode material.
5. The method for preparing the negative electrode material according to claim 4, characterized in that, In step S1, nano-silicon is immersed in a solution containing a catalyst precursor to obtain nano-silicon with a catalyst precursor attached to its surface. The nano-silicon with catalyst precursors attached to its surface is sintered in a hydrogen atmosphere and then calcined in an atmosphere containing carbon and nitrogen sources to obtain the Si@N-CNTs.
6. The method for preparing the negative electrode material according to claim 5, characterized in that, In step S1, the sintering temperature is 600~1200℃, and the sintering time is 1~10h; And / or, the calcination temperature is 600~1200℃, and the calcination time is 1~10h.
7. The method for preparing the negative electrode material according to claim 4, characterized in that, In step S2, before the impregnation, the method further includes: immersing the Si@N-CNTs in an acidic solution for impurity removal.
8. The method for preparing the negative electrode material according to claim 4, characterized in that, Step S2 includes at least one of the following features (1) to (5); (1) The lithium-ionizing agent includes elemental lithium, aromatic hydrocarbons, film-forming additives, and solvents; (2) The aromatic hydrocarbons include at least one of naphthalene and its derivatives, biphenyl and its derivatives, terphenyl and its derivatives, tetraphenyl and its derivatives, anthracene and its derivatives, phenanthrene and its derivatives, and naphthalene and its derivatives; (3) In the lithium-ionizing reagent, the content of the aromatic hydrocarbon is 0.01~20 mol%; (4) In the lithiumation reagent, the content of the film-forming additive is 0.01~1 mol / L; (5) The molar ratio of the elemental lithium to the aromatic hydrocarbon is (3~8):
1.
9. The method for preparing the negative electrode material according to claim 4, characterized in that, In step S2, the soaking time is 5 to 15 minutes.
10. A lithium-ion battery, characterized in that, Includes the negative electrode material as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Carbon nanotube / MOF-based silicon-carbon composite material as well as preparation method and application thereof
CN112216828A
Preparation and application of boron-nitrogen co-doped carbon nanotube coated silicon monoxide composite material
CN114899398A
